Sheep fattening value chain development in Goma Pilot Learning Woreda (PLW): IPMS experiences - Baredo, Y.; Tefera, T.L.; Tegegne, Azage; Hoekstra, Dirk (International Livestock Research Institute, 2013)
Traditionally, most smallholder farmers in Goma and elsewhere in Ethiopia engage in sheep and goat fattening to generate sufficient income to meet household requirements and other social obligations. A rapid assessment with IPMS project partners in Goma found that traditional sheep fattening is constrained by inadequate feed supply, low nutritive value of available feed resources, and lack of technical knowledge which resulted in prolonged fattening period and low economic return. Accidental death or loss of fattened animals for various reasons is another challenge for vulnerable smallholders, especially if sheep are purchased on credit. During discussion with various stakeholders, several potential interventions were identified to initiate a more commercially oriented small ruminant enterprise addressing some of the constraints with new interventions. These included i) reduced fattening periods through supplementary feed using locally available cotton seed meal (CSM), ii) piloting a community-based/managed livestock insurance scheme with 120 target farmers in Kilole PA, iii) introducing an innovative credit scheme through Oromia Credit and Saving Share Company (OCSSCo) for entrepreneurial fattening, and iv) introducing leguminous forage seed multiplication by model farmers. Meetings were held by the district OoA staff in some Peasant Associations to discuss identified problems and potential interventions. Subsequently, one pilot Peasant Association that agreed to include women in the program was selected. Other discussions/trainings were also held with farmers and project partners to develop community-based livestock insurance scheme and to increase knowledge and skills on supplementary feeding and forage (seed) production and selection of lambs for fattening. Following the value chain approach, linkages were created with the woreda veterinary services and an oil extraction factory in the District capital which produced cotton seed meal; this had never been used in the District before. We facilitated the linkage of target farmers with OCSSCo. Data were collected from all 120 target farmers using a questionnaire and group discussion. The study showed that more than 74% of the farmers managed to shorten the fattening period by 50%, i.e. from six months to three months. In the course of first cycle, 510 sheep were fattened of which 15 died. Thirteen (13) were immediately refunded by the community-based livestock insurance scheme and 2 claims were rejected by the livestock insurance capital managing committee based on conditions spelled out in the by-laws. Average return from five sheep in one cycle was about Ethiopian birr (ETB)1 450. Loan repayment by women participants was 100%, and some male farmers defaulted. Scaling out is taking place, which includes fattening more sheep per cycle by some entrepreneurial female farmers.